Exploration of Interaction and Mapping Interaction Research in Second Language Learning Content Analysis Based on Books Rod Ellis - Ahmad Fadhel Syakir Hidayat; Mamluatul Hasanah; Abdul Latif; Slamet Mulyani; Rifqi Aulia Rahman; Azwar Annas; Akhirudin (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This study examines the concepts of Interaction and Mapping Interaction Research in Second Language Learning in the Classroom: Content Analysis Based on Rod Ellis's